AN EVALUATION OF INFORMATION TECHNOLOGY MANAGEMENT OF ASSEST AND LOGISTIC MANAGEMENT BUREAU USING COBIT 4.1 (A Case Study : Informatics and Business Institute Darmajaya Bandar Lampung) - Yuni Puspita Sari (Prosiding International conference on Information Technology and Business (ICITB), 2015)
The use of information system application at supply andinventory department of MAL of IBI Darmajaya Lampungis the most important part of business processes of anenterprise serving all units especially serving employeesand lecturers, and monitoring and evaluating theperformance of information technology as well as themanagement to reach the effective and efficient goal of theorganization.Monitoring and Evaluation on a good performance can beconducted by auditing the existing system technicallyusing COBIT 4.1 framework and utility aspects usingmultiple gap as the standard in analyzing how muchattention of the management to the information system andhow the information system can fit the management needsfor information by looking at the importance andsatisfaction between management and users.From the audit process phase conducted in domainmonitoring and evaluation, it is necessary to get attentionbecause users expectation and management focus moreon the level of information technology performance whichstill needs improvement according to the specific standardin data management.KEY WORDS: Information System Application, Audit,COBIT, Multiple Gap analysis